(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The English language has become a worldwide phenomenon, a pervasive force in emancipation worldwide. The effects of knowing English and its function in bridging cultural gaps are discussed in the paper. Knowing English well increases job prospects in today’s global market. Native English speakers have an edge in breaking into the global labor market, working with multinational corporations, and engaging in international commerce. The language provides a springboard for upward economic and social mobility, allowing people and communities to raise their standard of living.